A modified Park-Ang model for seismic damage assessment of recycled aggregate concrete-filled square steel tube columns. (December 2022) - Peng, Sheng; Wang, Junyu; Yao, Yingkang; Min, Tianrun; Li, Chaoying; Luo, Le; Zhu, Yide; Wen, Xin; Zhou, Man
Abstract: This paper focuses on the seismic damage assessment mechanism of recycled aggregate concrete-filled square steel tube (RACFSST) columns via the seismic test results of 95 RACFSST column structures. Based on the dual criteria of deformation and energy, with consideration of the mechanical characteristics of RACFSST column structures, a modified Park-Ang model for seismic damage assessment of RACFSST columns was proposed by introducing the modified dissipation factor. The quantitative index of the performance-based seismic design of RACFSST columns was established, and the criteria of the damage performance level of RACFSST columns under different failure states were proposed. The results show that the modified Park-Ang damage model can reflect the seismic damage evolvement rule of RACFSST columns well. The seismic damage degrees of RACFSST columns can be divided into basically intact ( D =0–0.02), slightly damaged and moderately damaged ( D =0.02–0.41), severely damaged ( D =0.41–0.98) and collapsed ( D =0.98–1.00). Under the probabilistic reliability of 84.13%, the interlayer displacement angle limit of RACFSST columns at the corresponding five seismic performance levels were using normally ( D <1/150), using temporarily ( D =1/150), using after repair ( D =1/100), hardly ensuring life safety ( D =1/50) and preventing collapse ( D =1/35). The seismic damage assessment basis for RACFSST columns under different performance levels is made clearly by controlling the damage threshold.